2021
DOI: 10.1186/s12870-021-03246-5
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome and de novo analysis of Rosa xanthina f. spontanea in response to cold stress

Abstract: Background Rose is one of most popular ornamental plants worldwide and is of high economic value and great cultural importance. However, cold damage restricts its planting application in cold areas. To elucidate the metabolic response of rose under low temperature stress, we conducted transcriptome and de novo analysis of Rosa xanthina f. spontanea. Results A total of 124,106 unigenes from 9 libraries were generated by de novo assembly, with N50 le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The circadian clock of plants provides them with a competitive advantage in their living environment by regulating their physiological and metabolic rhythms. Circadian clocks are composed of transcription-translation feedback loops that are influenced by signals such as external temperature and light to adjust biological rhythms to match the environment [33,34]. In this study, 25 DEGs were enriched in the KEGG pathway "circadian rhythm-plant"; in the CA treatment group, Lanjian No.…”
Section: Role Of the Circadian Clock In The Cold Acclimation Responsementioning
confidence: 76%
“…The circadian clock of plants provides them with a competitive advantage in their living environment by regulating their physiological and metabolic rhythms. Circadian clocks are composed of transcription-translation feedback loops that are influenced by signals such as external temperature and light to adjust biological rhythms to match the environment [33,34]. In this study, 25 DEGs were enriched in the KEGG pathway "circadian rhythm-plant"; in the CA treatment group, Lanjian No.…”
Section: Role Of the Circadian Clock In The Cold Acclimation Responsementioning
confidence: 76%
“…The advent of high-throughput sequencing has facilitated the comprehensive exploration of the entire genome’s expression at the transcriptional level. Transcriptome sequencing has been conducted on various plants under low-temperature stress, encompassing model plants [ 21 24 ], horticultural plants [ 25 ], vegetable crops [ 20 ], and trees [ 26 ]. These studies offer insights into how transcriptional changes respond to cold stress, leading to the identification of numerous cold response genes across different crops.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that the significantly higher freezing tolerance in the shoot of R. beggeriana than that of R. fortuneana , which originated in southeastern China, might be due to the stronger ability of the spatial transfer of soluble sugars from leaves to shoots and consequently the storage of soluble sugars as starch in the shoots during overwintering [ 44 ]. The transcriptome analyses in R. multiflora and R. xanthina further indicated that the pathways of starch and sucrose metabolism were activated during cold stress [ 42 , 45 ]. However, it is not clear whether and which members of the SWEET gene family may participate in the cold response of a rose.…”
Section: Introductionmentioning
confidence: 99%